THE PROBLEMS CONCERNING REALIZATION OF POWERS BY THE SUBJECTS OF THE RUSSIAN FEDERATION (BY THE EXAMPLE OF THE REPUBLIC OF TATARSTAN) - L. Vasin, Alexander; V. Krasnov, Eduard (Gênero & Direito, 2019)
This paper discusses conceptual and applied issues regarding the agreements between the federal centre and the subjects of the Russian Federation on the division of jurisdiction and powers. The paper reveals the historical background and reasons for the emergence of this legal institution, its consolidation in the Constitution of the Russian Federation and the Constitution of Tatarstan, the evolution of current domestic legislation, as well as the practice of applying the above institution. It is indicated that the distinction between objects of jurisdiction and authority is an integral element of the principle of federalism, which is one of the foundations of the state system of the Russian Federation. Also, the paper provides an extensive historical retrospective of the evolution of state and legal relations between the Russian Federation and the Republic of Tatarstan. In many ways, it was the experience of these relationships that influenced the development of the legal framework for regulating the issue of the current study. The accumulated experience of the functioning of state authorities on the basis of such agreements is evaluated, and an opinion is expressed on maintaining the potential of this legal institution for improving federal relations. In addition, an opinion is expressed on the need to develop the correct and competent use of this mechanism, which will allow the best qualities of the domestic constitutional model to show and open up additional growth opportunities for individual regions